2013
DOI: 10.1177/1460458212462151
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with change in Internet usage of Swedish older adults (2004–2010)

Abstract: The increased reliance on Internet use in social functions has presumably left out a part of the population: the oldest-older adults. These are people who have not kept themselves up to date with the technological developments for various reasons. There are, however, exceptions from whom we have something to learn. This study investigates the older people in Sweden who started to use the Internet over a period of 6 years. Cognition, extraversion, openness, functional disability, household economy, sex, age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Studies have even suggested more awareness to create senior friendly websites, taking into account cognitive decline (26). Lower cognitive functioning has been related to not starting to use the Internet in old age (16). Some studies have highlighted that cognitive aspects are less understood than other age-related declines, when it comes to F o r P e e r R e v i e w 3 Internet use by older adults (27).…”
Section: Background (Factors Affecting Internet Usage Of Older-adults)mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have even suggested more awareness to create senior friendly websites, taking into account cognitive decline (26). Lower cognitive functioning has been related to not starting to use the Internet in old age (16). Some studies have highlighted that cognitive aspects are less understood than other age-related declines, when it comes to F o r P e e r R e v i e w 3 Internet use by older adults (27).…”
Section: Background (Factors Affecting Internet Usage Of Older-adults)mentioning
confidence: 99%
“…Being male, is a factor affecting older-adults' computer and Internet usage-even still in the last decade (16).…”
Section: Background (Factors Affecting Internet Usage Of Older-adults)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cognitive decline may be a barrier for older people to use Internet, which maybe more severe when getting old [25]. A longitudinal study from England suggests that Internet use may reduce cognitive decline [10].…”
Section: Journal Of Healthcare Communications Issn 2472-1654mentioning
confidence: 99%